Microalgae Growth and Phosphorus Uptake of Chlamydomonas Reinhardtii 11/32C under Different Inorganic Nitrogen Sources - Yulistyorini, Anie; Miller Alonso, Camargo-Valero (International Journal of Integrated Engineering, 2020)
Microalgae have been shown to be effective in utilizing both nitrogen and phosphorus from a wide range of wastewaters. This ability enhances the potential role that microalgae may have not only in wastewater bioremediation, but also in algal biomass production as an alternative feedstock for biofertiliser and biofuel production. This study was conducted to investigate the nutrient recovery from wastewater through microalgae biological uptake. The green microalgae of C. reinhardtii 11/32C used in this study and cultivated in Bold’s Basal Media (BBM). The algae culture was placed in a 2 liter of photobioreactor for approximately in 14 days. The results revealed that green microalgae can recover up to 5.9 % and 1.3% of N and P in their cell, respectively.